Complex patterns of the HIV-1 epidemic in Kuala Lumpur, Malaysia: Evidence for expansion of circulating recombinant form CRF3301B and detection of multiple other recombinants - Wang, B.; Lau, K.A.; Ong, L.Y.; Shah, M.; Steam, M.C.; Foley, B.; Dwyer, D.E.; Chew, C.B.; Kamarulzaman, A.; Ng, K.P.; Saksena, N.K. (2007)
The HIV protease-reverse transcriptase (PR-RT) (1047 bp), gp120-env (891 bp) and gp41-env (547 bp) regions from the plasma of 115 HIV-1-infected patients in Kuala Lumpur (KL), Malaysia were sequenced. Detailed phylogenetic and bootscanning analyses were performed to determine the mosaic structure of the HIV-1 strains and their recombination breakpoint(s). Among the 50 patient samples in which all three regions could be amplified, the HIV-1 CRF0 1AE subtype (46) was predominant followed by subtypes B (10) and B' (6). A total of 9/50 (18) patients were infected with a CR-F01AE/B inter-subtype recombinant, displaying a recombinant form (RF) PR-RT, CPF01AE(gp120-env) and CRF01AE(gp41-evn). This RF was derived from the Thai variants of CRF01AE and B' subtype, with two distinct B' subtype segments in the backbone of CRF01AE, similar to the newly identified CRF33-01 B. In addition, one sample demonstrated a close structural relationship with the new CRF3301B in the PR-RT region but displayed B' segment in part of the env region (RFPR-RT, CRF01AE/B'(gp120-env)) and B'(gp41-env)) indicating continuing evolution of CRF3301B. The remaining 18 of samples were identified as unique recombinant forms (URFs). (c) 2007 Elsevier Inc. All rights reserved.